The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/ol.2016.5104
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tumor volume changes and serial plasma osteopontin detection during radical radiotherapy of non-small-cell lung cancer

Abstract: Abstract. The prognostic quality of increased osteopontin (OPN) plasma levels has been demonstrated for the chemotherapy and surgery of lung cancer. There is also evidence in the literature that tumor volume impacts prognosis in definitive radiotherapy (RT) of (lung) cancer. We previously demonstrated that elevated plasma levels of OPN before, and increasing OPN plasma levels after RT significantly correlate with survival and outcome after curative-intent RT of non-small-cell lung cancer (NSCLC). Tumor volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the literature, the prediction of outcome based on GTV changes during RT remains inconclusive [4]. While some studies [15,18,19] reported a tumor volume reduction or the reduction ratio to be associated with improved OS or PFS after RT, others (Van Elmpt et al) could not confirm these results. There are also conflicting results indicating an inferior OS in patients with a higher tumor volume reduction during RT [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the prediction of outcome based on GTV changes during RT remains inconclusive [4]. While some studies [15,18,19] reported a tumor volume reduction or the reduction ratio to be associated with improved OS or PFS after RT, others (Van Elmpt et al) could not confirm these results. There are also conflicting results indicating an inferior OS in patients with a higher tumor volume reduction during RT [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, re-evaluation of GTV during RT was predominantly carried out between 40 and 50 Gy in order to adapt the treatment plan for tumor volume changes. Clinical evidence also suggests significant tumor volume changes after 30–50 Gy [ 17 , 18 ]. While no significant effect of relative GTV changes during RT on OS was found in our dataset, absolute GTV detected during RT between 40 and 50 Gy in our study significantly impacted OS in both the crude and the adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…They all correlated with clinical parameters associated with OS and a combined consideration of expression for those three markers was independently associated with poor outcome. Validation was then obtained in larger NSCLC cohorts, especially focused on OPN plasma levels [ 142 , 143 , 179 ]. HIF-1α serum levels in 80 patients harbouring NSCLC and undergoing chemoradiotherapy in a curative intent were assessed [ 137 ]: soluble HIF-1α levels were decreased during and after treatment compared to the initial point, suggesting serum HIF-1α concentrations as a potential marker to monitor tumour response during chemoradiation.…”
Section: Available Tools To Detect Hypoxia In Clinical Practicementioning
confidence: 99%
“…High OPN levels in plasma were associated with higher levels of hypoxia in tumors and a higher risk of recurrence in patients with early stage NSCLC (33). In individuals with advanced lung cancer, higher circulating OPN levels were associated with a poorer prognosis and worse therapeutic responses (34)(35)(36). Prior to this study, BALF and urine OPN levels had not been assessed.…”
Section: Discussionmentioning
confidence: 99%